137k views
4 votes
When solving the equation, which is the best first step to begin to simplify the equation?

-2(x+3)=-10

User John Powel
by
5.5k points

2 Answers

4 votes

Answer:

Explanation:

-2(x+3)=-10

Open the bracket

-2x - 6 = -10

Collecting like terms

-2x = -10 + 6

-2x = -4

Dividing through by -2

x = -4/-2

x = 2

User Loich
by
5.1k points
4 votes
The best first step is to distribute the -2 into the parentheses.

1) -2x-6=-10

Then add the 6 to both sides of the equation.

2) -2x=-4

Finally divide both sides by -2.

3) x=2
User Piphonom
by
5.6k points